Analisis Order Picking dengan Menggunakan Metode Routing Heuristics di Gudang PT. GMS - Chandra, Agung (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2015)
Order picking is the most labour and costly activities both in manual system and automated system. So, it is necessary to improve efficiency and productivity. One way to do is to reduce travel distance or travel time. Time can be reduced by implementing routing heuristics method which has the shortest distance, and shorter distance means less energy consumption and fit to greener warehousing concept. The research at PT. GMS, Jakarta shows the routing method – Midpoint, The Largest Gap, and Combined – dynamic programming are the most efficient method